Aerodynamic analysis of wind turbine flows using open source software - Liu, Jiye. (2014)
Chapter 2, briefly describes the basic aerodynamics theory of Horizontal Axis Wind Thrbines (HAWT). General aerodynamic concepts and the operation of airfoils are introduced. This chapter provides a glimpse of the classical aerodynamic methods review and the most useful definitions, appearing in the following entire thesis, are explained.